PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS MELALUI MODERATING STRUKTUR MODAL pada Perusahaan Food and Beverages yang terdaftar di BEI periode 2010-2013 - Mirza, Refi; ', Zulbahridar; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the effect of Managerial Ownership Structure on profitability, the effect size of the Company to Profitability and through moderating capital structure of the two independent variables on profitability indirectly. The samples determined by purposive sampling method in order to obtain a sample of 15 food and beverage companies in the Indonesia Stock Exchange. The data were analyzed using Multiple Linier Regression , Classical Assumption Test and Test of Hypothesis. Partial test results can be concluded that the Managerial Ownership structure has an influence on profitability. It can be seen the value of 2,601 t and p value (sign) 0.012, < 0,05 so H1 accepted. After moderated capital structure obtained by value t count equal to 3,827 and p value (sign) 0.000 < 0.05 so that H2 is accepted. Variable Size concluded the company has no influence on profitability after visits t 0.809 and p value (sign) 0.442> 0.05, including after by moderating capital structure, H3 and H4 is rejected. And Capital Structure has an influence on the profitability of which 2,085 t and p value (sign) 0.042 < 0.05 so H5 accepted.Keywords: Manajerial Ownership Structure, Company Size, Capital Structure and Return On Assets.